Integration of Tuberculosis (TB) Screening in The Ryan White Program in Arkansas - Gu, Mofan (Open Forum Infect Dis, 2017)
BACKGROUND: Globally, TB remains the most common cause of death among people with HIV (killing 1 in 4 patients). In the US, the conservative estimate of HIV-LTBI burden is 48,000. Population-based TB-HIV data are not available due to inadequate TB screening among the HIV-infected. In the previous study we found that recommendation for TB screening is missing in HIV guidelines in 36 out of 50 (72%) US states, and TB screening data are missing in half of the Ryan White Programs. METHODS: We aim to assess the current surveillance structure and prevalence of TB screening among Ryan White clients in Arkansas, and inform revisions of guidelines. We interviewed ADH staff (including Ryan White program manager, data specialist, Infectious Disease branch manager, and TB epidemiologist) to map out how TB screening is supposed to be reported in the Ryan White Program. We also assessed data availability and quality in both CAREWare and electronic client dossiers. After evaluation, we created a user-defined data field in CAREWare for pilot testing. Then we had meetings involving both the Ryan White Program and the TB Program for discussion. RESULTS: The data flow is shown in Figures 1 and 2. We found no TB screening files in Ryan White client dossiers. The existing TB data structure in CAREWare is confusing, with duplicate variables (both active and inactivate) in multiple sub-tabs. We proposed a user-friendly data field for TB screening (date, type of tests, result, and interpretation). We made three policy changes at the ADH: a memorandum of understanding between the Ryan White Program and the TB Program to improve communications, a modified contract (effective March 2017) with Ryan White providers that mandates annual TB screening for all clients, and an official letter to all physicians in Arkansas addressing the importance of TB screening among HIV-infected people. CONCLUSION: We believe that program collaboration and service integration between TB and HIV is the key in eliminating missed opportunities in TB-AIDS diagnoses. In our next steps, we want to evaluate the data captured in CAREWare between 2016 and 2017. We also want to question why individual level data, which should include TB screenings, are not reported to the HRSA. DISCLOSURES: All authors: No reported disclosures.